2023
DOI: 10.3390/nu15081975
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Coverage of Severe Acute Malnutrition Treatment with a Simplified Protocol in a Humanitarian Context in Diffa, Niger

Abstract: Background: the aim of this study is to evaluate the effectiveness and coverage of a simplified protocol that is implemented in health centers (HCs) and health posts (HPs) for children who are suffering from severe acute malnutrition (SAM) in the humanitarian context of Diffa. Methods: We conducted a non-randomized community-controlled trial. The control group received outpatient treatment for SAM, without medical complications, at HCs and HPs with the standard protocol of community management of acute malnutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This similarity persisted even after employing the shared gamma frailty model ( P = 0.575), indicating clustering or heterogeneity in both SAM and MAM groups. These findings are consistent with previous studies conducted in various regions of Africa, supporting the consistency of non-inferiority in average length of stay and time to cure between simplified and standard treatment approaches ( 8 11 , 14 , 39 ). These findings altogether have strong programmatic and policy implications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This similarity persisted even after employing the shared gamma frailty model ( P = 0.575), indicating clustering or heterogeneity in both SAM and MAM groups. These findings are consistent with previous studies conducted in various regions of Africa, supporting the consistency of non-inferiority in average length of stay and time to cure between simplified and standard treatment approaches ( 8 11 , 14 , 39 ). These findings altogether have strong programmatic and policy implications.…”
Section: Discussionsupporting
confidence: 92%
“…In studies conducted in various regions of Africa, the duration of treatment and recovery time for children with acute malnutrition using a modified dosage was similar to the standard protocol ( 8 11 , 14 , 39 ). In this study, we set out to compare the recovery time of a simplified approach with the standard protocol in the treatment of acute malnutrition (specifically uncomplicated SAM and MAM in children aged 6–59 months) to provide context-specific evidence for treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of treating one child with SAM was USD 31.4 in Kabléwa and USD 21.2 in the simplified protocol area. It is worth noting that the reduction in dose did not appear to have a negative impact on recovery rates [13]. The modelled scenario sensitivity analysis showed that, all other things being equal, the difference in RUF costs remains, thus providing robust evidence for cost savings in terms of RUF where the simplified protocol was used.…”
Section: Discussionmentioning
confidence: 78%
“…In 2021, Action Against Hunger, in collaboration with the Centre de Recherche Médicale et Sanitaire in Niger (CERMES), the Nutrition Division of the Ministry of Health in Niger and EPINUT research group from the Complutense University of Madrid (Spain), conducted an operational research project comparing effectiveness of acute malnutrition treatment with a standard and simplified protocol decentralised to the village level in an emergency context in Diffa region, Niger. In this study, the recovery rate among children treated with a simplified protocol was 96.6% while the recovery rate among those treated with the standard protocol was 87% [13]. In the latter group, children were required to recover based on two criteria (MUAC and WHZ), while recovery of children in the simplified protocol group was by MUAC only.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation